Type IIA topoisomerase (TOP2A) triggers epithelial-mesenchymal transition and facilitates HCC progression by regulating Snail expression. Issue 2 (20th December 2021) - Dong, Yinying; Sun, Xiangyin; Zhang, Kong; He, Xinjia; Zhang, Qian; Song, Hao; Xu, Mingjin; Lu, Haijun; Ren, Ruimei
ABSTRACT: Type IIA topoisomerase (TOP2A) is upregulated in hepatocellular carcinoma (HCC) and its expression is positively correlated with poor prognosis. However, the underlying molecular mechanism of this connection are poorly understood. Hence, the present work aimed to examine the possible mechanisms which may be useful in identifying a potential therapeutic strategy. The differential expression of TOP2A mRNA in HCC as compared with adjacent normal tissue was analyzed using the Oncomine database. The expression levels of TOP2A in HCC specimens and cell lines were assessed by Western blot and RT-qPCR. Stable cell lines were generated to knockdown or overexpress TOP2A, and then cell growth, migration, and invasion were analyzed. Furthermore, this study examined epithelial-mesenchymal transition (EMT) as well as the activation of related pathways. Additionally, the correlation between TOP2A levels and E-cadherin/Snail expression was determined in 72 HCC specimens. Higher expression levels of TOP2A were observed in HCC in Oncomine datasets, and the results were verified using 40 pairs of HCC specimens and peritumoral tissues. TOP2A expression levels were remarkably elevated in cells with great metastatic capacity. In addition, HCC cell growth, migration, and invasion were suppressed after TOP2A knockdown in MHCC97H cells (MHCC97H-shRNA-TOP2A), while these capabilities were promoted in TOP2A-overexpressing Hep3B cells (Hep3B-TOP2A). Furthermore, EMT was inhibited in MHCC97H-shRNA-TOP2A cells, but induced in Hep3B-TOP2A cells. The induction of EMT by TOP2A was shown to be mediated by Snail, as TOP2A promoted Snail expression through the p-ERK1/2/p-SMAD2 signaling pathway. TOP2A level showed a negative correlation with E-cadherin, whereas a positive correlation with that of vimentin and Snail in human HCC specimens by immunohistochemistry analyses. Kaplan–Meier survival curves revealed that TOP2A upregulation showed a positive correlation with poor prognosis patients. Taken together, TOP2A possibly enhances the metastasis of HCC by promoting EMT through the mediation of the p-ERK1/2/p-SMAD2/Snail pathway. This indicates that TOP2A maybe a potential factor to predict the prognosis of HCC.